Developing a social life cycle assessment tool for micro and small scale jewelry industry in the Philippines in the case of Meycauayan City, Bulacan - Gonzales, Dyan C.; Soriano, Virginia Jose (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
In this study, the Social Life Cycle Assessment framework is created by adapting the Life Cycle Assessment framework and the ISO framework in which Study Design Parameters are utilized. Social aspect is incorporated to be able to recommend a set of guidelines and instruments that may be used in the Philippines. At present, UNEP is still developing the guidelines of Social Life Cycle Assessment so UNEP call for contributions from different countries based on their current situations and conditions. The S-LCA is adapted in the case of jewelry industry. In order to obtain the potential social impacts in a system boundary, a survey instrument was used to obtain the related information from different stakeholders, i.e. workers, consumers/clients, local community, local government, society and non-government organizations, and value chain actors. The survey questionnaires were constructed based on the book entitled "Guidelines for Social Life Cycle Assessment of Products" by UNEP 2009. These questionnaires are further developed in which questions are adapted based on the Philippines settings and policy. The instruments and guidelines that were developed are applied in the case of micro and small scale jewelry industry in Meycauayan, Bulacan. This study identifies the social impact categories that have positive, negative and neutral social impact to different stakeholder, workers, consumers, value chain actors and society. For workers, the impact categories that have positive social impact are health and safety child labor, forced labor, discrimination, employment relationship, training and education, and job satisfaction and engagement. On the other hand, the impact categories that have negative social impact are wages and social benefits. Working hour has a neutral social impact. Work-life balance and freedom of association and collective bargaining are not observed in micro and small scale jewelry industries. For consumers and value chain actors, both health and safety and experienced well-being have positive social impact. For society, which includes the local government, non-government organizations and local community, all the impact categories (health and safety, community engagement, access to tangible resources, employment, and local capacity building) have positive social impact. The case study shows the feasible application of the developed instruments and guidelines for micro and small scale jewelry industry. This study is the first S-LCA in the Philippines that considers the impacts to different stakeholders of some impact categories in the case of micro and small scale jewelry industry. The database and instrument created in this study may help the future researchers in conducting S-LCA of the other industries in the Philippines. Also, Social Hot Spots database for jewelry industry is established based on the output of this study.
Thesis (M.S. Industrial Engineering)--University of the Philippines Diliman
Keywords: Jewelry trade -- Philippines; Social life cycle assessment (S-LCA).